2020
DOI: 10.1093/jncics/pkaa052
|View full text |Cite
|
Sign up to set email alerts
|

Male Sex and the Risk of Childhood Cancer: The Mediating Effect of Birth Defects

Abstract: Background There is a persistent, unexplained disparity in sex ratio among childhood cancer cases, whereby males are more likely to develop most cancers. This male predominance is also seen for most birth defects, which are strongly associated with risk of childhood cancer. We conducted mediation analysis to estimate whether the increased risk of cancer among males is partially explained by birth defect status. Methods We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
1
8
1
1
Order By: Relevance
“… 10–12 However, a recent study suggests that birth defects may act as a strong mediator, explaining up to 40% of the association between sex and childhood cancer. 13 …”
Section: Introductionmentioning
confidence: 99%
“… 10–12 However, a recent study suggests that birth defects may act as a strong mediator, explaining up to 40% of the association between sex and childhood cancer. 13 …”
Section: Introductionmentioning
confidence: 99%
“…The ratio of males to females was 1.26: 1. In general, it is known that male children are at greater risk of developing cancer than their female counterpart [12]. However, the exact mechanisms that underlie this difference in childhood cancer incidence by sex is mostly unknown [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these anomalies associated with BWS have also been associated with an increased HB risk and it has been suggested that individuals with BWS may represent some of the established HB risk factors [43]. A recent population-based study demonstrated that birth defects can mediate the relationship between childhood cancer and male sex predominance, with strong mediation effects identified specifically for hepatoblastoma and among children younger than one year at time of any cancer diagnosis [44].…”
Section: Discussionmentioning
confidence: 99%